A spatial-temporal decorrelating receiver for CDMA systems with base-station antenna arrays. - Ruifeng Wang (IEEE Transactions on communications)
We investigate multiuser signal detection with a base-station antenna array for a synchronous DS-CDMA uplink using nonorthogonal codes in Rayleigh fading channels. We have developed a new formulation for a spatial-temporal decorrelating detector using the maximum-likelihood criteria. The detector is shown to be near-far resistant. We propose to implement the spatial-temporal decorrelating receiver iteratively by applying the space-alternating generalized expectation-maximization (SAGE) algorithm. Simulation results show that the SAGE-based decorrelating receiver significantly outperforms the conventional single-user receiver and with performance close to that of a spatial-temporal decorrelating receiver with known channel parameters. We have observed that adding base-station antennas can actually improve convergence of the proposed iterative receiver